“No princípio era o ato”: totalização e falha de Lacan a Marx - Maia, Álvaro Lins Monteiro (2022)
This work aims to support the thesis that the act, as conceptualized by the french psychoanalyst Jacques Lacan, based on the psychoanalytic act as the 'end of analysis', or as a passage from analysant to analyst, in a psychoanalysis, and in homology with the revolutionary act, as can be adduced from Karl Marx's position in relation to his theory of capital, that this act, therefore, occupies a precarious and empty place of cause, in relation to the processes of subjectivation and social formation, which in Lacan can be traced in the paths of renunciation and recovery of jouissance and which emerge as the production of surplus-jouissance, a term coined from jouissance in psychoanalysis (and which refers to Freud's 'Lust') and also from Marx's surplus-value, keeping with the latter a structural equality that allows considering surplus-enjoyment and surplus-value as homologous, similarity to the homology between psychoanalytic act and revolutionary act. The position of the act as that which occupies the empty and obfuscated place of the cause in relation to the production of surplus-jouissance responds, in a general extrapolation of the notion of act, to the effect of subject as fundamentally divisive, and if, at the same time , the act is produced as a result of the processes of renunciation and recovery of jouissance, this production retroactively finds the structure of this effect of subject as a statutory division that, in the end, in turn, produces itself. This stance, as opposed to another that unilaterally considered the act only as a result of the production of surplus-jouissance, has the advantage of not risking dissolving the effect of division, which constitutes the very structure of the act, in the processes of signification, whose consequence is the masking of the subject's constitutive failure, and therefore, the neutralization of the most important outcomes of psychoanalysis and social struggle. For this reason, as a result of the conclusions drawn from it, this thesis allows, at the same time, to rethink, not without precedent, the paths of revolutionary theory within the Marxist tradition, in addition to the paths of psychoanalysis itself in times of its dissolution into a therapeutics of adaptation to markets.